Development and Evaluation of an Efficient Second Order Non-Linear Optical Single Crystal – 2-(3-Aminopyridinium-1-yl)-3-Carboxy-Proponate Monohydrate - G, Saravana Kumar; M, Jeyalaxmi (Photonics Letters of Poland, 2023)
A slow evaporation solution approach was used to create high-quality single crystals of 2-(3-aminopyridinium-1-yl)-3-carboxyproponate monohydrate (3ACPM). The single crystal X-ray diffraction was used to determine the crystal system and lattice characteristics. Software called Krystal Shaper was used to mimic the morphology of the 3ACPM. To evaluate the optical transmittance, UV-vis spectral analysis was used. The Nd:YAG laser was used to assess the laser-induced surface damage threshold (LISDT) of 3ACPM single crystal. The presence of second harmonic generation (SHG) was evaluated using the Kurtz-Perry powder method. Full Text: PDF References Y. Zhang, H. Li, B. Xi, Y. Che,vJ. Zheng, "Growth and characterization of l-histidine nitrate single crystal, a promising semiorganic NLO material", Mater. Chem. Phys. 108, 192 (2008), CrossRef S. Draguta, M.S. Fonari, A.E. Masunov, J. Zazueta, S. Sullivan, M.Y. Antipin, T.V. Timofeeva, "New acentric materials constructed from aminopyridines and 4-nitrophenol", Cryst. Eng. Comm. 15, 4700 (2013) CrossRef G. Peramaiyan, R. Mohan Kumar, "Nonlinear optical and laser damage threshold studies of an ammonium p-toluenesulfonate crystal", Appl. Phys. A 119, 707 (2015), CrossRef G.M. Corrales, D. Morales-Morales,S. Hernandez-Ortega, J.J. Campos-Gaxiolaa, A. Cruz Enrıquez, "2-(3-Aminopyridinium-1-yl)-3-carboxypropanoate monohydrate", Acta Cryst. E68, o853 (2012), CrossRef S.K. Kurtz, T.T. Perry, "A Powder Technique for the Evaluation of Nonlinear Optical Materials", J. Appl. Phys. 39, 3798 (1968), CrossRef S. Panchapakesan, K. Subramani, B.Srinivasan, "Growth, characterization and quantum chemical studies of an organic single crystal: 3-Aminopyridine 4-Nitrophenol for opto-electronic applications", J. Mater. Sci: Mater. Electron. 28, 5754 (2017), CrossRef